2015
DOI: 10.1039/c5sm00662g
|View full text |Cite
|
Sign up to set email alerts
|

Composite bottlebrush mechanics: α-internexin fine-tunes neurofilament network properties

Abstract: Neuronal cytoplasmic intermediate filaments are principal structural and mechanical elements of the axon. Their expression during embryonic development follows a differential pattern, while their unregulated expression is correlated to neurodegenerative diseases. The largest neurofilament proteins of medium (NF-M) and high molecular weight (NF-H) were shown to modulate the axonal architecture and inter-filament spacing. However, the individual roles of the remaining α-internexin (α-Inx) and neurofilament of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 48 publications
1
58
0
Order By: Relevance
“…6H). Similar chain interpenetration behavior has been reported for protruding neurofilament side arms, which are also unstructured polyampholytes, at high osmotic pressures (68)(69)(70).…”
Section: )]mentioning
confidence: 54%
“…6H). Similar chain interpenetration behavior has been reported for protruding neurofilament side arms, which are also unstructured polyampholytes, at high osmotic pressures (68)(69)(70).…”
Section: )]mentioning
confidence: 54%
“…In particular, it suggests that specific cross-linking is involved in the unusually short spacing observed between composite filaments composed of NF-M and NF-L proteins. A recent study, applying the same model to composite networks of a-Inx and the NF triplet, demonstrated a wider spacing is found between composite filaments composed of NF-M and a-Inx proteins [181]. This trend is opposite to the mean field expectation, as a-Inx is both shorter, less charged and more hydrophobic than NF-L, and therefore would not be expected to increase the inter-filament spacing [131].…”
Section: Tail-to-tail Inter-filament Attractive and Repulsive Interacmentioning
confidence: 96%
“…2C), in which the stretched grafted end forms the ''stem'' of the flower-like tip [129][130][131]. Alternatively, strong surface or adjacent polymer attractions may prevent the formation of the outer ''flower'' corona and will result with preferable collapsed configuration, termed ''truffle conformation'' [132] (Fig. 2D).…”
Section: Theoretical Modeling Of Polymer Brushesmentioning
confidence: 99%
“…1982;LiemandHutchison 1982;JulienandMushynski 1983; Hirokawa et al 1984; Nakagawa et al 1995; Chen et al 2000; Rao et al 2002b, 2003). Finally, recent evidence indicates that α-internexin fine-tunes the NF network through increasing interfilament spacing (Kornreich et al 2015). …”
Section: Nf Protein Domain Structure and Assemblymentioning
confidence: 99%